Hot Deformation Behavior of a Novel Near-β Titanium Alloy Ti-5.5Mo-6V-7Cr-4Al-2Sn-1Fe in (α+β) Phase Region - Gai, Jinyang; Cheng, Jun; Li, Jinshan; Du, Zhaoxin; Zhang, Wen; Yu, Sen; Yu, Zhentao (Frontiers in Materials, 2020)
The hot deformation behavior of a novel near-beta titanium alloy Ti-5.5Mo-6V-7Cr-4Al-2Sn-1Fe in (α+β) phase region in the temperature of 605~755℃ and strain rate range of 10-3~10-1/s-1 was investigated on the Gleeble-3800 thermo-mechanical simulator. The results showed that the deformation parameters can have a significant influence on flow softening behavior and the microstructure evolution, as well as dynamic recrystallization is remarkable at temperature 755℃and strain rate 10-3s-1. The flow stress decreases with the increase of temperature and decrease of strain rate. With the rise of temperature and strain rate, the content of α phase gradually decreases. During the thermal deformation process, the α phase content decreases with the increase of the strain rate and the size of α phase decreases with increasing temperature. αGB is short rod or spherical. Andα phase precipitated after short-term aging preferentially nucleated within the grains after aging treatment. Moreover, the thermal-mechanical process does not induce α phase generation compared to general heat treatment.